2020
DOI: 10.1136/gutjnl-2020-321767
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 acts as a lipid metabolism regulator contributing to inflammation and carcinogenesis in non-alcoholic fatty liver disease

Abstract: ObjectiveReceptor-interacting protein kinase 3 (RIPK3) is a key player in necroptosis execution and an emerging metabolic regulator, whose contribution to non-alcoholic fatty liver disease (NAFLD) is controversial. We aimed to clarify the impact of RIPK3 signalling in the pathogenesis of human and experimental NAFLD.DesignRIPK3 levels were evaluated in two large independent cohorts of patients with biopsy proven NAFLD diagnosis and correlated with clinical and biochemical parameters. Wild-type (WT) or Ripk3-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 46 publications
7
92
1
Order By: Relevance
“…This process is initiated by death receptors or PPRs, including TLRs, and needs from RIPK1 and RIPK3 proteins to be executed, among others ( 48 ). RIPK3 has emerged as a metabolic regulator and its role as a key manager of metabolism, damage, inflammation, fibrosis and even carcinogenesis has been recently proven ( 49 ).…”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%
“…This process is initiated by death receptors or PPRs, including TLRs, and needs from RIPK1 and RIPK3 proteins to be executed, among others ( 48 ). RIPK3 has emerged as a metabolic regulator and its role as a key manager of metabolism, damage, inflammation, fibrosis and even carcinogenesis has been recently proven ( 49 ).…”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%
“…10 Accordingly, we have recently shown that Ripk3-deficient mice display increased levels of liver glycogen compared with wild-type counterparts upon a dietary model of NAFLD. 26 RIPK3 also directly targets and activates glutamate ammonia ligase (GLUL) and glutamate dehydrogenase 1 (GLUD1), which catalyses the conversion of glutamate and ammonia to glutamine in cytosol and glutamate to α-ketoglutarate in mitochondria, respectively. In turn, both α-ketoglutarate and glutamine metabolism also feed the TCA cycle, powering OXPHOS and overproduction of the oxidative metabolism product, ROS.…”
Section: Mitochondrial Metabolic Homeostasismentioning
confidence: 99%
“…Further, we have recently shown that RIPK3 depletion in mice is associated with increased activity of liver MRC complexes in experimental NASH, with the concomitant increase of citrate synthase activity, a TCA enzyme, 5 but strikingly this phenotype was accompanied by decreased ROS production. 26 With the restoration of defective MRC complex activity in Ripk3-deficient mice, overall mitochondrial metabolic homeostasis was also enhanced by Ripk3 deficiency, followed by increased mitochondrial biogenesis and fatty-oxidation markers. 5 Thus, activation of MRC complexes is a novel indication of RIPK3-mediated mitochondrial energy metabolism regulation, considering the central role of MRC complexes on the electron transport chain and that defects in MRC complexes lead to ROS overabundance.…”
Section: Mitochondrial Metabolic Homeostasismentioning
confidence: 99%
See 2 more Smart Citations